Inflammasomes in placental explants of women with preeclampsia cultured with monosodium urate may be modulated by vitamin D - Nunes, Priscila Rezeck [UNESP]; Romao-Veiga, Mariana [UNESP]; Ribeiro, Vanessa Rocha [UNESP]; de Oliveira, Larissa Ragozo Cardoso [UNESP]; de Carvalho Depra, Igor [UNESP]; de Oliveira, Leandro Gustavo [UNESP]; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha Serrao [UNESP] (Taylor & Francis, 2022)
Objectives: Preeclampsia (PE) is an important syndrome of gestation characterized by placental and systemic inflammation. High plasma concentration of uric acid are frequently associated with inflammation and endothelial dysfunction and may contribute to PE pathogenesis. This study aimed to evaluate the vitamin D (VD) immunomodulatory effect on the NLRP1/NLRP3 inflammasomes in placental explants from preeclamptic (PE) and normotensive (NT) pregnant women. Study design: Placental explants from 10 late-onset PE (LOPE), 10 early-onset PE (EOPE), and 10 NT pregnant women were cultured with or without monosodium urate (MSU) and VD. Main outcome measures: Gene and protein expression of NLRP1, NLRP3, HMGB1, caspase-1, interleukin-1 beta (IL-1β), and IL-18 were determined by quantitative PCR and Western blotting/ELISA. Statistical significance was accepted at p < 0.05. Results: Basal gene and protein expression of NLRP1/NLRP3 and IL-1β, IL-18 and HMGB1 were significantly higher in explants from EOPE compared to LOPE and NT pregnant women. In addition, culture with MSU increased these inflammatory markers, and concomitant treatment with MSU+VD decreased this effect. Conclusions: The results demonstrated that NLRP1 and NLRP3 inflammasomes are upregulated in the placental tissue of EOPE women, associated with high production of inflammatory cytokines. The in vitro treatment with VD downregulated placental inflammasomes induced by MSU, suggesting its immunomodulatory role in the systemic inflammation of PE.
Keywords: cytokines; inflammasome; MSU; placental explants; Preeclampsia; vitamin D